Identification of spectral biomarkers for type 1 diabetes mellitus using the combination of chiroptical and vibrational spectroscopy - Šťovíčková, Lucie; Tatarkovič, Michal; Logerová, Hana; Vavřinec, Jan; Setnička, Vladimír (The Analyst, 2015)
The current diagnostic tools are insufficient for the early detection of many diseases, including type 1 diabetes mellitus. The disease is accompanied not only by a permanently elevated level of blood glucose and altered levels of other biomarkers, but also by changes in the conformation of blood plasma proteins and other biomolecules associated with the pathogenesis of diabetes. However, the observation of these structural changes by conventional Raman and infrared spectroscopy is limited. Therefore, we used chiroptical spectroscopy which is inherently sensitive to the 3D structure of chiral molecules and able to detect any possible structural changes. We investigated the blood plasma samples of diabetic patients and healthy controls by Raman optical activity and electronic circular dichroism. The measurements were combined with conventional methods of molecular spectroscopy, i.e. Raman and infrared spectroscopy. The obtained data sets were statistically evaluated using linear discriminant analysis focusing on the spectral ranges that correspond to the structure and conformation of proteins and other plasmatic biomolecules. Our results suggest that chiroptical spectroscopy gives more detailed information about the 3D structure of biomolecules; and therefore, might be a promising complement to conventional diagnostic methods.
Keywords: vibrace; spektrální analýza; Diabetes Mellitus, Type 1; Young Adult; Spectrum Analysis; studie případů a kontrol; Case-Control Studies; Humans; Biomarkers; Vibration; lidé; mladý dospělý; biologické markery; Adolescent; Discriminant Analysis; diskriminační analýza; diabetes mellitus 1. typu; mladiství